Enzymes Involving in Chocolate Processing - Kiyat, Warsono El; Monica, Audrey; Qomariyah, Noor; Manurung, Brian Saputra (Fakultas Farmasi, Universitas Gadjah Mada, 2018)
Indonesia is one of the largest cocoa-producing countries in the world, but the productivity of Indonesian cocoa is relatively low compared to other cocoa-producing countries. Many cocoa beans are exported in raw form (raw cocoa beans) so they do not have high economic value. In addition, cocoa beans also can not be consumed directly and must be processed first. The processing of cocoa beans includes curing stage, breaking the fruit, fermentation, soaking and washing, drying, sorting, and storage to producing cacao almonds. The fermenting process of cocoa beans involves the role of the polyphenol oxidase to produce flavor precursor compounds. Furthermore, to improve the quality of the resulting chocolate, protease and carboxypeptidase can be used in the processing of cacao almonds to enhance flavor precursor compounds forming to produce chocolate with stronger flavor characteristics. Processed chocolates can be developed into confectionery with a soft or liquid filler by utilizing invertase to obtain a solid filler during processing that may turn into liquid during storage.Â Keywords : cocoa, chocolate, enzyme, processing.